China's growing conflict with the WTO: The case of export restrictions on rare earth resources - Brigid Gavin (Intereconomics, 2013)
China is the leading exporter of rare earths, elements which are crucial to the development of high-tech products and new green technologies. In recent years, however, China has begun imposing export restraints on these elements in order to benefi t its domestic economic development. This reduces global supply and thus artifi cially leads to higher prices for importing countries. The EU, the US and Japan have launched a formal complaint in the WTO against China's export restrictions. China claims that these restrictions are aimed at environmental protection. This paper examines China's rare earth policy and its compliance with WTO rules.
Keywords: 330; Kritische Metalle; Außenhandel; WTO-Recht; Handelskonflikt; Geopolitik; China